2022
DOI: 10.1186/s12885-022-09548-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarker SGSM1 and its correlation with immune infiltration in gliomas

Abstract: Objective Glioma was the most common type of intracranial malignant tumor. Even after standard treatment, the recurrence and malignant progression of lower-grade gliomas (LGGs) were almost inevitable. The overall survival (OS) of patients with LGG varied widely, making it critical for prognostic prediction. Small G Protein Signaling Modulator 1 (SGSM1) has hardly been studied in gliomas. Therefore, we aimed to investigate the prognostic role of SGSM1 and its relationship with immune infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Nomograms can graphically describe biological information, characteristics, and clinical variables as a statistical prediction model and estimate the individualized risk according to the characteristics of patients and diseases. It is a simple, easy-to-understand, and user-friendly clinical decision-making tool ( 41 ) and was widely used in individualized prognostic evaluation of breast cancer ( 42 ), rectal cancer ( 43 ), prostate cancer ( 44 ), glioma ( 45 ), and lung adenocarcinoma ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms can graphically describe biological information, characteristics, and clinical variables as a statistical prediction model and estimate the individualized risk according to the characteristics of patients and diseases. It is a simple, easy-to-understand, and user-friendly clinical decision-making tool ( 41 ) and was widely used in individualized prognostic evaluation of breast cancer ( 42 ), rectal cancer ( 43 ), prostate cancer ( 44 ), glioma ( 45 ), and lung adenocarcinoma ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…2f, left). The most differentially expressed gene EMP3 (Epithelial membrane protein 3), which has been identified as an tumor suppressor in breast cancer [34], glioma [35] and remains to be elucidated in colon cancer. The characteristic genes in malignant epithelial cell populations were found to be involved in biological processes such as matrix remodeling, cell proliferation and apoptosis (Fig.…”
Section: Transcriptional and Functional Features Of Malignant Cells R...mentioning
confidence: 99%
“…Furthermore, the expression of small G protein signaling modulator 1 (SGSM1) tended to be relatively diminished in low-grade glioma tissues. The downregulation of SGSM1 expression was found to be associated with poor survival time in patients with either low-grade glioma or its subtypes [ 5 ]. Numerous studies have confirmed a significant correlation between sulfatases (SULF) and cancer [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed correlations between changes in the expression of specific long non-coding RNAs/genes and the growth/metastasis of cancer [2][3][4][5][6]. For example, Ge et al, found an association between the overexpression of tumor protein p53 inducible protein 13 (TP53I13) in glioma tissues and unfavorable survival outcomes.…”
Section: Introductionmentioning
confidence: 99%